PERANCANGAN MONITORING SUHU BERBASIS INTERNET OF THINGS DENGAN NODE MCU ESP8266, DHT 11 DAN THINGSPEAK - Fahrus Salam; Onki Alexander (JURNAL ILMIAH INFORMATIKA, 2023)
Monitoring temperature is an aspect that we need to know so that we can know the standard of temperature and humidity in a place. The purpose of this study is that we monitor temperature and humidity levels in real-time, so an Internet of Things (IoT) based Temperature Monitoring Design is made for DHT11 temperature and humidity sensors whose data can be acquired using the NodeMCU ESP8266 microcontroller connected to the internet or wifi. sent to ThingSpeak as the data-receiving server. After the data is entered into Thingspeak, the measurement data that has been carried out can be viewed using a cellphone or computer. The data obtained is then displayed in the form of temperature and humidity graphs, these graphic displays can be accessed online on the Thingspek web